The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.ajog.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic management of neuropathic pain

Abstract: Obstetrician/gynecologists often are the initial management clinicians for pelvic neuropathic pain. While treatment may require comprehensive team management and consultation with other specialists, there a few critical and basic steps that can be performed on an office visit that offer the opportunity to significantly improve quality of life in this patient population. A key first step is a thorough clinical examination to physically map the pain site and identify potentially involved nerves. Only limited evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 100 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…These results are in line with recent in vitro analyses in MCF-7 cells, which show that the activation of ERα36 expression triggers adaptive changes characterized by enhanced survival and migration during acquired tamoxifen resistance process [8, 21]. Similar data were obtained from endometrial cancer cells wherein ERα36 was shown to promote tamoxifen agonist action via the MAPK/ERK and PI3K/Akt pathways [2224]. Taken together, our results and others clearly suggest that [ER+] tumors highly expressing ERα36 should not be cured by tamoxifen because the treatment could drive metastatic progression.…”
Section: Discussionsupporting
confidence: 86%
“…These results are in line with recent in vitro analyses in MCF-7 cells, which show that the activation of ERα36 expression triggers adaptive changes characterized by enhanced survival and migration during acquired tamoxifen resistance process [8, 21]. Similar data were obtained from endometrial cancer cells wherein ERα36 was shown to promote tamoxifen agonist action via the MAPK/ERK and PI3K/Akt pathways [2224]. Taken together, our results and others clearly suggest that [ER+] tumors highly expressing ERα36 should not be cured by tamoxifen because the treatment could drive metastatic progression.…”
Section: Discussionsupporting
confidence: 86%
“…This lack of training makes the diagnosis of acute iatrogenic nerve injury unlikely in the immediate postoperative period when early intervention is important for improving outcome. 8 , 10 , 11 Our team recognizes that this manuscript does not provide sufficient detail for rapid dissemination and clinical adaptation. Our primary objective was to highlight the clinical implications of our collective research and development efforts to date in order to lay the foundation for future technique- and method-specific manuscripts.…”
Section: Discussionmentioning
confidence: 99%
“… Adapted from work by Frank F. Tu, Kevin M. Hellman, Miroslav M. Backonja, Titled Gynecologic management of neuropathic pain, 106 copyright of Elsevier, 2011. Used by permission of Elsevier from the Copyright Clearance Center's Rights Link.…”
Section: Diagnosismentioning
confidence: 99%